A multidisciplinary investigation of a mummified Egyptian head and analysis of its associated resinous material from the Salinas Regional Archaeological Museum in Palermo (Sicily) - Squires, Kirsty; Davidson, Alison; Cooper, Simon; Viner, Mark; et al. (Elsevier, 2024)
Among the 70 items donated by the abbot Antonio Pietro Paternostro to the former National Museum of Palermo (now Salinas Regional Archaeological Museum) in 1870, an ancient Egyptian mummified human head stands out. In 2022 the finding was submitted for a multidisciplinary investigation that relied upon non-invasive or minimally invasive approaches. Investigations revealed that this is a possible female head, which was likely subjected to trans-nasal craniotomy, and dated to the Egyptian Graeco-Roman period. The head was packed with an abundant amount of resin which was analysed using thermogravimetric analysis, infrared spectroscopy, and gas chromatography with mass spectrometry. The analysis suggested that the resin was most likely comprised of a natural resin, pitch, or tar, from the Pinaceae family of conifers, and mixed with other materials including a fat, oil, or wax. The use of multiple sample preparation techniques for the chromatographic analysis provided a high level of confidence in the identification of a wide variety of compounds, including a range of himachalene derivatives, which indicate the inclusion of cedar tar or oil.
Keywords: Biological anthropology; Mummification; Resin; Radiocarbon dating; TGA; FTIR; GC-MS